2016
DOI: 10.1090/ecgd/294
|View full text |Cite
|
Sign up to set email alerts
|

Conical limit points and the Cannon-Thurston map

Abstract: Abstract. Let G be a non-elementary word-hyperbolic group acting as a convergence group on a compact metrizable space Z so that there exists a continuous G-equivariant map i : ∂G → Z, which we call a Cannon-Thurston map. We obtain two characterzations (a dynamical one and a geometric one) of conical limit points in Z in terms of their pre-images under the Cannon-Thurston map i. As an application we prove, under the extra assumption that the action of G on Z has no accidental parabolics, that if the map i is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…In particular, if the Cannon-Thurston map ι : ∂H → ∂G exists, then this map is unique and for any sequence h n ∈ H ∪ ∂H converging to some X ∈ ∂H in the topology of H ∪ ∂H, we have lim n→∞ h n = ι(X) in G ∪ ∂G. It is known, see [30, Proposition 2.12], that if H is a non-elementary word-hyperbolic subgroup of a word-hyperbolic group G, then a map ∂H → ∂G is the Cannon-Thurston map if and only if this map is continuous and H-equivariant.…”
mentioning
confidence: 99%
“…In particular, if the Cannon-Thurston map ι : ∂H → ∂G exists, then this map is unique and for any sequence h n ∈ H ∪ ∂H converging to some X ∈ ∂H in the topology of H ∪ ∂H, we have lim n→∞ h n = ι(X) in G ∪ ∂G. It is known, see [30, Proposition 2.12], that if H is a non-elementary word-hyperbolic subgroup of a word-hyperbolic group G, then a map ∂H → ∂G is the Cannon-Thurston map if and only if this map is continuous and H-equivariant.…”
mentioning
confidence: 99%
“…H is the set of ideal points of lifts of almost minimizing geodesic rays. Theorem 1.3 answers an issue that has come up in works of several authors [Kap95,Ger12,JKLO16] who tried to relate the injective points of the Cannon-Thurston map to the conical limit set. They concluded that the conical limit set is strictly contained in the set of injective points of the Cannon-Thurston map.…”
Section: Introductionmentioning
confidence: 92%
“…We remark that H and G are hyperbolic groups with H a non-elementary subgroup of G, then if the Cannon-Thurston map ∂i : ∂H → ∂G exists, then for each h ∈ H of infinite order, ∂i(h ∞ ) = lim n→∞ (i(h)) n . Additionally, in this setting where H is non-elementary, if f : ∂H → ∂G is a continuous and H-equivariant map, then f must be the Cannon-Thurston map (Proposition 2.12 [37]).…”
Section: The Cannon-thurston Mapmentioning
confidence: 99%
“…Note also that if H is a quasiconvex subgroup of a hyperbolic group G, then the Cannon-Thurston map trivially exists (and is injective on ∂H), since geodesic rays with bounded Hausdorff distance in Γ H will map to quasi-geodesic rays which have bounded Hausdorff distance in Γ G . In fact, it is known that the Cannon-Thurston map ∂i : ∂H → ∂G is injective if and only if H is a quasiconvex subgroup of G (see Proposition 2.13 [37] and Lemma 2.1 [51]).…”
Section: The Cannon-thurston Mapmentioning
confidence: 99%